Use of Hydrosurgical Debridement System for Silicone Gel Removal after Breast Implant Rupture - Alessandro Scalise, MD; Alberto Pau, MD; Caterina Licini, MSc, PhD; Donatella Brancorsini, MD; Monica Mattioli Belmonte Cima, MSc, PhD; Gaia Goteri, MD, PhD; Giovanni Di Benedetto, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2024)
Summary:. Breast implant rupture is one of the most common complications in aesthetic and reconstructive surgery. Furthermore, this problem is closely linked to capsular contracture. It is therefore crucially important to effectively and promptly remove silicone leakage from breast pockets. Several techniques are described in the literature and have been typically used for this procedure. Hydrosurgical debridement (HD), which is usually applied in wound care to treat wounds, could be useful for the removal of the silicone leaked from prosthesis pockets after breast implant rupture. An entire periprosthetic capsule that contained a ruptured implant with silicone leakage was removed from a left breast. Half of the capsule was treated with HD, whereas the other half was left untreated as a control. Samples were processed by light microscopy and scanning electron microscopy for morphological analyses. light microscopy demonstrated that the nontreated tissues had a typical synovial-like structure with a middle layer of connective tissue in which there were numerous rounded empty spaces which contained silicone. In contrast, the superficial connective region of the treated tissues (T) had fewer and flattened spaces where the silicone was detected. Scanning electron microscopic analysis showed that in the T samples, the capsule thickness was compact compared with that of the nontreated tissues. Furthermore, the fibrous components appeared well organized with few and smaller silicone lacunae. HD is useful for the removal of silicone (ex vivo) from capsular surfaces after implant rupture. Because of its safety characteristics, this technique could be successfully used in vivo.